Caracterización estructural, histológica y espectral del cultivo de tuna (opuntia ficus-indica) en el cantón Latacunga, provincia de Cotopaxi 2013 - Simba Tul, Norma Patricia (2014)
A research study on “Structural, Histological, and Spectral Characterization of ‘Tuna’ (Opuntia ficus-indica)”, was carried out in Guaytacama Parish, Latacunga Canton, Cotopaxi Province, during the year 2013. The general purpose of this study was to generate, systematize, and standardize the graphic and spectral information on digital media of the macro and micro structures of ‘Tuna’, for academic and research applications. The study was conducted using high resolution images captured with high-tech equipment. It allowed for identification of each part of the plant, followed with didactic theoretical information. An interactive website that is user-friendly was designed. Three fundamental aspects were taken into account. Firstly, a structural characterization using a 46-megapixel SIGMA camera with 3 RGB sensors and a 250mm zoom lens visualized macro structural images. It showed the basic characteristics of the plant (roots, steam, leaves, flowers, fruit, and seed).